2022
DOI: 10.1186/s13063-022-06615-z
|View full text |Cite
|
Sign up to set email alerts
|

Early essential newborn care for cesarean section newborns in China: study protocol for a multi-centered randomized controlled trial

Abstract: Background Early essential newborn care (EENC) is a package of evidence-based and cost-effective interventions delivered around birth mainly including delayed cord clamping, immediate and sustained skin-to-skin contact, and early initiation of exclusive breastfeeding. EENC is proven effective in promoting breastfeeding and improving women’s and newborns’ health. However, there is little evidence on implementation of EENC on newborns born by cesarean section in China. Therefore, the objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The World Health Organization (WHO) recommends that mother-infant skin-to-skin contact (SSC) should begin with direct contact with the mother's bare skin within 1 minute of birth [1]. Multiple randomized controlled studies have found the importance of cesarean SSC for breastfeeding [2][3][4]. CUI Xiaomei et al [5] conducted a randomized controlled study on the effectiveness of SSC immediately after birth and SSC within 1 hour after birth on breastfeeding duration, initiation and duration of first breastfeeding, time to initiation of lactation II, breastfeeding self-efficacy scores, breastfeeding acceptance and satisfaction scores, and rates of exclusive breastfeeding at 24, 48, 72 hours and 42 days postpartum were significantly better in the spontaneous delivery immediate SSC group than that in the 30-minof-birth initiation SSC control group.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that mother-infant skin-to-skin contact (SSC) should begin with direct contact with the mother's bare skin within 1 minute of birth [1]. Multiple randomized controlled studies have found the importance of cesarean SSC for breastfeeding [2][3][4]. CUI Xiaomei et al [5] conducted a randomized controlled study on the effectiveness of SSC immediately after birth and SSC within 1 hour after birth on breastfeeding duration, initiation and duration of first breastfeeding, time to initiation of lactation II, breastfeeding self-efficacy scores, breastfeeding acceptance and satisfaction scores, and rates of exclusive breastfeeding at 24, 48, 72 hours and 42 days postpartum were significantly better in the spontaneous delivery immediate SSC group than that in the 30-minof-birth initiation SSC control group.…”
Section: Introductionmentioning
confidence: 99%